The Effects of Youth Labor Market Reforms: Evidence from Italian Apprenticeships - Andrea Albanese; Lorenzo Cappellari; Marco Leonardi (Università Cattolica del Sacro Cuore, Dipartimento di Economia e Finanza (DISCE), 2017)
This paper estimates the causal effects of the 2003 reform of the Italian apprenticeship contract which aimed at introducing the "dual system" in Italy by allowing on-the-job training. The reform also increased the age eligibility of the apprenticeship contract and introduced a minimum floor to apprentices' wages. Using administrative data and balancing techniques we find that five years after hiring, the new contract improves the chances of moving to a permanent job in the same firm, yet this happens mostly in large firms. There are also sizeable long-run wage effects of the reform, well beyond the legal duration of apprenticeships, compatible with increased human capital accumulation probably due to the training provisions of the reform.
Keywords: J24; J41; C21; 330; Apprenticeship; Permanent Work; Youth Employment; Covariate Balancing; Propensity Score